Land Readjustment for Regularization of Informal Settlements - Manandhar, Robina (Journal of Science and Engineering, 2019)
Regularization of informal settlements involves the process of legalization of tenure and upgrading of public services and infrastructures through land development. However, some settlement manages to get the services from formal authorities but lags legal tenure security. Legalization of tenure security is important so as to reduce their threat of eviction from formal authorities and improvement of their living standard. Various land development tools involves upgrading of public services and development of infrastructures but legalization of tenure security is left behind. Land development and legalization of tenure security both are the important components for regularization of informal settlements and recognize as formal settlements. Land readjustment is the tool or technique commonly used for the land development in Nepal. Thus this paper aims to indentify the applicability of land readjustment in regularization of informal settlement. In Nepal, there are prominent numbers of informal settlements along the river banks and also in urban core areas. Chadani tole along the Bagmati River is taken as a case study and analysis of applicability of land readjustment under the social and legal condition for regularization is carried out. This research has adopted both desk research and case study methodology. Qualitative and quantitative data analysis is adopted in this study. The results of research reveal that public participation and long term occupancy are the social positive aspects for the application of LR in informal settlements. Lack of land registration, legal recognition and development regulations are the legal hurdles for the application of LR in informal settlements. Land registration of informal settlement has not been done in Nepal which is important aspect for application of LR. Thus land registration of Nepal should include the components of STDM for the pro poor land registration and recognition of social tenure to informal settlements. Applicability of LR is difficult due to the lack of sufficient area. So to address the issue and ascertain the rights of dwellers to live in the same area, high rise apartments can be adopted.